2022
DOI: 10.1111/ppl.13619
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to different light intensities affects emission of volatiles and accumulations of both pigments and phenolics in Azolla filiculoides

Abstract: Many agronomic trials demonstrated the nitrogen‐fixing ability of the ferns Azolla spp. and its obligate cyanobiont Trichormus azollae. In this study, we have screened the emission of volatile organic compounds (VOCs) and analyzed pigments (chlorophylls, carotenoids) as well as phenolic compounds in Azolla filiculoides–T. azollae symbionts exposed to different light intensities. Our results revealed VOC emission mainly comprising isoprene and methanol (~82% and ~13% of the overall blend, respectively). In part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 119 publications
0
6
0
Order By: Relevance
“…ABA increases significantly, carotenoid precursors of ABA decrease, and isoprene remains largely unaffected under moderate to severe droughts (Tattini et al, 2014;Perreca et al, 2020). Such correlations or lack thereof may indicate age-and stress-driven prioritisation of certain isoprenoids when carbon reserves (de novo and older) are in short supply (Rasulov et al, 2014;Dani et al, 2016;Brilli et al, 2022). However, genetic suppression of isoprene emission in unstressed plant leaves significantly changes the carbon distribution within the MEP pathway by favouring more carotenoid synthesis (Ghirardo et al, 2014), but significantly less plastidic cytokinins (Fig.…”
Section: Volatiles As Chemical Conspecifics Of Hormones: Volatile Iso...mentioning
confidence: 99%
“…ABA increases significantly, carotenoid precursors of ABA decrease, and isoprene remains largely unaffected under moderate to severe droughts (Tattini et al, 2014;Perreca et al, 2020). Such correlations or lack thereof may indicate age-and stress-driven prioritisation of certain isoprenoids when carbon reserves (de novo and older) are in short supply (Rasulov et al, 2014;Dani et al, 2016;Brilli et al, 2022). However, genetic suppression of isoprene emission in unstressed plant leaves significantly changes the carbon distribution within the MEP pathway by favouring more carotenoid synthesis (Ghirardo et al, 2014), but significantly less plastidic cytokinins (Fig.…”
Section: Volatiles As Chemical Conspecifics Of Hormones: Volatile Iso...mentioning
confidence: 99%
“…Our photochemistry measurements confirm that, in A. filiculoides, photosynthesis is optimized under low light conditions [10,11] as, consistent with the results of Shi and Hall [49], the light-curve response of the ETR saturates at an intensity of only 400 µmol m −2 s −1 , regardless of the growing temperature. Moreover, the same analyses confirmed that Azolla can successfully adapt to an increasing light intensity [12,50], although this adaptation highly depends on the temperature. In our experiments, exposure to a higher light intensity (700 µmol m −2 s −1 ) reduced the content of chlorophyll in A. filiculoides grown at 25 • C, although this did not affect the photochemical processes of photosynthesis assessed through fluorescence measurements (under both light and dark conditions).…”
Section: Genome Mining and Expression Analysis Of The Flavonoid Pathw...mentioning
confidence: 60%
“…The sustained growth of Azolla is supported by high CO 2 photosynthetic assimilation rates [9]. Although Azolla requires low light to saturate the electron transport rate (ETR) and optimize photosynthesis [10,11], it can acclimate to higher light intensities [12]. This effect occurs through an efficient non-photochemical quenching process, which dissipates excess light energy in the form of heat [13].…”
Section: Introductionmentioning
confidence: 99%
“…The main functions attributed to stress-induced red flavonoid pigment accumulation in land plants are photoprotection by filtering blue/green light, and ROS-scavenging (Davies et al, 2022). Consistently, excess light triggered DA-accumulation in A. filiculoides (Brilli et al, 2022), often in combination with abiotic stresses such as nutrient deficiency or cold (Tran et al, 2020;Costarelli et al, 2021). Prolonged cold-exposure may distort the carbon and nitrogen cycling within the symbioses and cause photooxidative damage that may result in starvation of the host.…”
Section: Introductionmentioning
confidence: 94%